Subverting the Gaze, Seducing with the Bible: A Study of Oscar Wilde's Salomé - Dąbrowska, Justyna (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2014)
The present article engages with the eponymous character of Oscar Wilde’s “Salomé” and focuses on her subversion of the patriarchal rules, and on her attempts at seducing the prophet Jokanaan. Wilde’s “Salomé” becomes “an erotic symbol of daring, transgression, and perversity” (Sloan 112). She wants to look at Jokanaan, as well as to be touched by him and openly states her great desire for him, using the imagery taken from the biblical “Song of Songs” to express her passion. Moreover, the Princess skillfully adopts and reverses the male gaze to manipulate others and go beyond the patriarchal constraints at Herod’s court. She becomes aware that the only way to reach her goals is to look actively and evade being a mere object of the male gaze. The article shows that the imagery employed in the eponymous character’s speeches contributes to her portrayal as a seductress, also accentuating her rebellion, and analyzes how the Princess transgresses the patriarchal constraints through appropriating the male gaze.